KRITISISME KANT: RELEVANSINYA BAGI TEOLOGI ISLAM DAN KEMISKINAN - Novian Widiadharma; Muhammad Arif (UIN Sunan Kalijaga Yogyakarta, 2016)
Poverty is the real phenomena within Indonesian Muslim communities. In order to be actual, Islamic Theology should give the answer to this real problem within ummah i.e. the problem of poverty. The question is could the theology to answer the problem of poverty? This research tries to reflect to Criticism developed by Immanuel Kant. By its criticism Kant successfully answer the question whether the metaphysics as a science is possible? However finally Kant tends to reject the validity of the metaphysics as a science, he still accepts the principle of synthesis a priori as a mode of science. In order to make Islamic Theology discourses could answer the problem of poverty, the Islamic Theology should learn from Kant criticism project. The Islamic Theology should move from a priory approach to synthetic a priory approach. Because without the support of historical-empirical approach in the social sciences, the a priori-ahistoris character of lslamic Theology toward social facts will never able to answer the problem ofpoverty within Indonesian Muslim communities.